Vernacular globalisations: neo-statist accountability policies in France and Quebec education. Issue 1 (2nd January 2017) - Maroy, Christian; Pons, Xavier; Dupuy, Claire
Abstract: The article argues that there is no single globalisation of education systems, but rather multiple globalisations of each system taken in its individual context. We propose three explanatory factors to account for these vernacular globalisation processes, that is, for individual policy trajectories in each national context: path dependence on earlier policy choices and institutions, education policy-making through bricolage, and finally the translation by national actors of international-level ideas or tools as a function of the debate, institutions or national power dynamics in question. The research design is based on the study of a most-likely case: accountability policy in two school systems – France and Quebec – which show strong variations. Document analyses and semi-structured interviews were conducted in both cases. In the two countries, distinct vernacular globalisations are at work leading to different neo-statist accountability policies. In Quebec, the reinforcement of state power through a growing vertical accountability and the systematic development of regulation tools between policy actors and levels lead to a 'centralisation by institutional linkage'. In France, we rather witness a 'globalisation by discursive internalisation' in which transnational imperatives are integrated in official discourses on the regulation of the education system, but without radically questioning the mainstays of this regulation.